RISIKO, PROFITABILITAS, PERTUMBUHAN ASET, DAN ASET TETAP TERHADAP KEBIJAKAN DIVIDEN DAN KEBIJAKAN UTANG - ., Michael; Wijaya, Liliana Inggrit (Journal of Management and Business, 2010)
The aim of this study is to analyze the factors that influence financing policy. Financing policy as the independent variable consist of dividend anddebt policies. The factors that influence the dividend policy are business risk, profitability, and growth. Debt policy influence by dividend, business risk,profitability, and fixed asset. Toestimate relation between these factors, this study used Seemingly Unrelated Regression (SUR) because the debt and dividend model have same error term. Research object are companies in manufacture industry that listing in Indonesian stock Exchange that paid dividend in minimum 4 periods in research periods. The result of the analysis indicates that profitability have a significant influence toward dividend policy. Result for debt policy are business risk, profitability, and fixed asset have a significant influence toward debt policy. The result also shows that profit has positive significant effect to dividend, which indicates the ability of the firm to pay higher dividend while their profit increased. Risk and profit also show positive effect to debt. Firms with higher profit will have higher debt, however their risk also increased in significant positive relationship.